Peran kritis pengelolaan risiko reputasi dalam keberlanjutan bisnis - Annisa, Maulidya (Maliki Interdisciplinary Journal, 2025)
Corporate reputation plays a crucial strategic role in ensuring long-term sustainability. With a holistic approach, it is known that reputational risk impacts stakeholders’ views, financial results, ease of obtaining funding, and the attractiveness of the company in recruiting and retaining top human resources. The purpose of this article is to highlight the importance of reputation risk management in supporting business sustainability. In the midst of the digital era and information disclosure, reputation is a crucial asset that is vulnerable to external threats. The research in this article was conducted using literature study research through theoretical studies and other related reference sources. Based on the article that has been made by the author, the author finds the causes and strategies that are carried out to manage integrated reputation risk so that the company is able to maintain public trust and maintain its business continuity.